In support of practice-based teacher professional learning - Jeram, R.; Davids, N. (South African Journal of Higher Education, 2020)
Research indicates that teacher education programmes are impeded by abstract, theory-laden and decontextualised modes of teacher professional development. As a result, teachers have particular sets of pedagogical knowledge without a clear understanding of how this knowledge ought to be implemented in diverse classroom settings. As an alternative response, an argument is made for a practice-based teacher professional learning approach. By analysing theories around practice (practice theory) and the concept professional learning, we propose, firstly, that teacher professional learning programmes should include pedagogies for learning that are continuous, intensive, socially mediated, supportive, embodied and relate to the contextual needs of the teacher. Secondly, that teachers ought to be provided with the skills, necessary for the conversion of theoretical ideas into practice. Thirdly, we contend that a practice-based teacher professional approach requires teacher agency in relation to their practices, as opposed to merely implementing various strategies and approaches.